488 Superiority of Craniotomy Over Supportive Care for Octogenarians and Nonagenarians in Operable Acute Traumatic Subdural Hematoma. (1st March 2022) - Duehr, James; Puccio, Ava; Deng, Hansen; Hamilton, D. Kojo; Okonkwo, David O.; Nwachuku, Enyinna L.
Abstract : INTRODUCTION: The neurosurgical evacuation acute subdural hematoma in elderly trauma patients is controversial. We analyzed impact of craniotomy for acute subdural hematoma on survival in patients greater than eighty years of age. METHODS: Study population included patients aged 80 years and older who presented with acute traumatic SDHs between September 1, 2015 and January 1, 2020, and had radiographic findings indicating operative eligibility (i.e. midline shift >5mm and/or overall thickness >10mm). 104 patients met inclusion criteria. 35 received craniotomy and 69 were treated with supportive measures due to family/patient wishes or surgeon's professional decision. Comparative statistics and a Poisson regression adjusted for the influence of covariates were used. RESULTS: Of 35 craniotomy patients, 21 (60.00%) were deceased at 2 years of follow-up, compared to 48 (69.57%) deceased out of 69 control patients. No significant demographic differences existed between the two groups, other than age (craniotomy patients were younger; median age 84 vs 86; p < 0.001). In outcomes, the craniotomy cohort survived longer and in higher proportions (p = 0.028; Gehan-Breslow-Wilcoxon test). When adjusting for covariates, this effect became more pronounced: surgical patients died at 41.1% the rate of non-surgical ones. Of all the covariates, only initial GCS had a significant impact on the protective effect of craniotomy. In a logarithmic relationship, each point higher on initial GCS was associated with less benefit from surgery. CONCLUSION: The results presented here indicate a surgical benefit for this elderly cohort, consistent with prior findings of benefit in the setting of severe traumatic aSDH. Patients with worse neurologic impairment, i.e. low GCS, had the greatest survival benefit for surgical intervention.